The Role of The EphrinB2-EphB4 Bidirectional Signalling on Bone Remodeling: A Review - Zhou Qinghui; Chew Weiyun; Tang Hanqing; Suresh V Chinni (Malaysian Journal of Science (MJS), 2025)
Postmenopausal osteoporosis is a prevalent disease that can lead to serious outcomes such as fractures. Oestrogen deficiency during menopause and postmenopause increases bone turnover, with elevated bone resorption and formation. However, resorption surpasses formation, resulting in bone loss. Identifying intervention targets in bone physiology to restore bone remodeling balance and normal bone mass is the initial aim in developing new effective therapies. Currently, EphrinB2/EphB4, one of the membrane coupling factors between osteoclasts (OCs) and osteoblasts (OBs), is a prominent topic in bone disease research. However, the regulatory mechanisms of EphrinB2-EphB4 bidirectional signalling on OC and OB and its effects remain incompletely understood. This review seeks to clarify the physiological roles and mechanisms of known EphrinB2-EphB4 bidirectional signalling in bone remodeling, providing insights for future studies on modulating this signalling pathway.